2023
DOI: 10.3390/nu15030784
|View full text |Cite
|
Sign up to set email alerts
|

Oral Temperature and pH Influence Dietary Nitrate Metabolism in Healthy Adults

Abstract: This study tested the hypothesis that the increases in salivary and plasma [NO2−] after dietary NO3− supplementation would be greater when oral temperature and pH were independently elevated, and increased further when oral temperature and pH were elevated concurrently. Seven healthy males (mean ± SD, age 23 ± 4 years) ingested 70 mL of beetroot juice concentrate (BR, which provided ~6.2 mmol NO3−) during six separate laboratory visits. In a randomised crossover experimental design, salivary and plasma [NO3−] … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…Salivary and plasma [NO 3 − ] and [NO 2 − ] were not different between pre-supplementation baseline measures during the morning, afternoon, and evening experimental testing sessions. Consistent with previous research (Bailey et al 2016 ; Cocksedge et al 2023 ; Burleigh et al 2018 ; Woessner et al 2016 ), both salivary and plasma [NO 3 − ] and [NO 2 − ] increased following the acute ingestion of BR in the present study. However, contrary to the experimental hypothesis, the increases in salivary and plasma [NO 3 − ] and [NO 2 − ] after BR supplementation were consistent across the morning, afternoon, and evening.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Salivary and plasma [NO 3 − ] and [NO 2 − ] were not different between pre-supplementation baseline measures during the morning, afternoon, and evening experimental testing sessions. Consistent with previous research (Bailey et al 2016 ; Cocksedge et al 2023 ; Burleigh et al 2018 ; Woessner et al 2016 ), both salivary and plasma [NO 3 − ] and [NO 2 − ] increased following the acute ingestion of BR in the present study. However, contrary to the experimental hypothesis, the increases in salivary and plasma [NO 3 − ] and [NO 2 − ] after BR supplementation were consistent across the morning, afternoon, and evening.…”
Section: Discussionsupporting
confidence: 93%
“…In addition to SFR, salivary pH can impact oral NO 3 − reduction. Specifically, increasing salivary pH after NO 3 − supplementation has been reported to increase salivary and plasma [NO 2 − ] (Cocksedge et al 2023 ). Since both unstimulated SFR (Dawes 1975 , 1972 ) and salivary pH (Choi et al 2017 ; Ferguson and Fort 1974 ) exhibit circadian rhythms, with an acrophase in the afternoon, oral NO 3 − reduction and the resultant increases in salivary and plasma [NO 2 − ] after NO 3 − supplementation may be greatest in the afternoon.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Cocksedge et al [ 34 ] reported that independently increasing or lowering oral temperature or increasing oral pH significantly increased mean salivary NO 2 − after NO 3 − supplementation in healthy adults. In this experiment, seven healthy men consumed 70 mL/day of beetroot juice (which has about 6.2 nM NO 3 − ) during six separate laboratory visits.…”
Section: Dietary Sources Of Nitratementioning
confidence: 99%
“…Fresh beetroot fresh juice is most commonly used for nitrate supplementation, but it has a lower concentration compared to other beetroot products ( Table 2 ). Nevertheless, various studies have demonstrated a significant increase in nitrite levels (a marker of NO) in plasma after intake of beetroot juice [ 23 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ].…”
Section: Dietary Sources Of Nitratementioning
confidence: 99%
See 1 more Smart Citation